Magnesium-permeable TRPM6 polymorphisms in patients with meningomyelocele - Sarac, Mehmet; Onalan, Ebru; Bakal, Unal; Tartar, Tugay; Aydin, Mustafa; Orman, Aysen; Kazez, Ahmet (Springer International Publishing Ag, 2016)
Background: To evaluate whether there is an association between single nucleotide polymorphisms in magnesium-permeable TRPM6 ion channel and development of meningomyelocele (MMC). Therefore, we examined a total of 150 children with MMC, along with age-and gender-matched controls. DNA collected from whole blood was analyzed for the presence of two polymorphisms, rs2274924 (A > G; K1579E; Leu1579Glu) and rs3750425 (G > A; Val1393Ile), in TRPM6. Serum Mg2+ and calcium levels were also examined. Results: A statistically significant difference in the distribution of rs2274924 genotypes (p = 0.049) was observed between the groups. Decreases in the AA genotype, and increases in the AG heterozygous genotype were also detected in the study group. The distribution of polymorphisms in the rs3750425 genotype and alleles was not statistically different between groups. Serum Mg2+ levels were lower in the GG genotype of rs3750425 compared with the GA and AA genotypes (p = 0.003). Conclusions: A statistically significant difference in rs3750425 genotypes was observed between the patients with MMC and the controls, which corresponded to lower serum Mg2+ concentrations in these patients. Taken together, these results suggest that genetic variations in the Mg2+-permeable TRPM6 ion channel may play a role in the etiopathogenesis of MMC during embryonic development.
Keywords: Neural tube defect; Spina bifida cystica; Etiopathogenesis; Genetic; Embryogenesis; Development; Human; Children